Motor development of children with attention deficit hyperactivity disorder - Neto, F.; Goulardins, J.; Rigoli, Daniela; Piek, Jan; de Oliveira, J. (Associacao Brasileira de Psiquiatria, 2015)
Objective: To compare both global and specific domains of motor development of children with attention deficit hyperactivity disorder (ADHD) with that of typically developing children. Methods: Two hundred children (50 children with clinical diagnoses of ADHD, according to the DSM-IV-TR and 150 typically developing controls), aged 5 to 10 years, participated in this crosssectional study. The Motor Development Scale was used to assess fine and global motricity, balance, body schema, and spatial and temporal organization. Results: Between-group testing revealed statistically significant differences between the ADHD and control groups for all domains. The results also revealed a deficit of nearly two years in the motor development of children with ADHD compared with the normative sample. Conclusion: The current study shows that ADHD is associated with a delay in motor development when compared to typically developing children. The results also suggested difficulties in certain motor areas for those with ADHD. These results may point to plausible mechanisms underlying the relationship between ADHD and motor difficulties.